Causal Relationship Between Lung Function and Atrial Fibrillation: A Two Sample Univariable and Multivariable, Bidirectional Mendelian Randomization Study - Zhang, Qiaoyun; Zhang, Xiaoyu; Zhang, Jie; Wang, Biyan; Meng, Xiaoni; Tian, Qiuyue; Zhang, Jinxia; Jiang, Mengyang; Zhang, Yiqiang; Zheng, Deqiang; Wu, Lijuan; Wang, Wei; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Observational studies have identified impaired lung function accessed by forced expiratory volume in one second (FEV1), forced vital capacity (FVC) or the ratio of FEV1 over FVC (FEV1/FVC) as an independent risk factor for atrial fibrillation (AF). However, the result may be affected by confounders or reverse causality. Methods: We performed univariable MR (uvMR), multivariable MR (mvMR) and bidirectional two-sample MR to jointly estimate the causality of lung function with AF. Apart from the inverse variance weighted (IVW) approach as the main MR analysis, three complementary sensitive analyses approaches including MR-Egger regression, weighted median (WM) MR and Pleiotropy Residual Sum and Outlier (MR-PRESSO) in uvMR as well as mvMR-Egger and mvMR-PRESSO in mvMR were applied to control for pleiotropy. Linkage disequilibrium score (LDSC) regression was applied to estimate genetic correlation between lung function and AF. Results: All forward and reverse uvMR analyses consistently suggested absent causal relations between lung function and AF risk [forward IVW: odds ratio (OR)FEV1 = 1.031, 95% CI = 0.909–1.169, P = 0.630; ORFVC = 1.002, 95% CI = 0.834–1.204, P = 0.982; ORFEV1/FVC = 1.076, 95% CI = 0.966–1.199, P = 0.182; reverse IVW: ORFEV1 = 0.986, 95% CI = 0.966–1.007, P = 0.187; ORFVC = 0.985, 95% CI = 0.965–1.006, P = 0.158; ORFEV1/FVC = 0.994, 95% CI = 0.973–1.015, P = 0.545]. The forward MR-Egger showed that each standard deviation (SD) increase in FEV1/FVC was related to a higher AF risk (OR = 1.502, 95% CI = 1.178–1.915, P = 0.006) without heterogeneity (Q_pval = 0.064), but pleiotropy effect exist (intercept = −0.017, P = 0.012). However, this significant effect disappeared after adjustment of FEV1 and FVC (OR = 1.523, 95% CI = 0.445–5.217, P = 0.503) in mvMR. No evidence was found for independent causal effects of FEV1 and FVC on AF in mvMR analysis by using mvIVW method (ORFEV1 = 0.501, 95% CI = 0.056–4.457, P = 0.496; ORFVC = 1.969, 95% CI = 0.288–13.474, P = 0.490). Notably, the association between lung function and AF were replicated using the FinnGen cohort data. Conclusions: Our findings reported no coheritability between lung function and AF, and failed to find substantial causal relation between decreased lung function and risk of AF. However, lung function and AF were both associated with inflammation, which may be potential pathway, warranting further study.